Diet and Liver Adiposity in Older Adults: The Multiethnic Cohort Adiposity Phenotype Study. Issue 11 (29th September 2021) - Kaenkumchorn, Tanyaporn K; Merritt, Melissa A; Lim, Unhee; Le Marchand, Loïc; Boushey, Carol J; Shepherd, John A; Wilkens, Lynne R; Ernst, Thomas; Lampe, Johanna W
ABSTRACT: Background: Diet plays a key role in the pathogenesis of nonalcoholic fatty liver disease. Limited data exist regarding specific nutrients and food groups and liver fat continuously, particularly among different ethnicities. Objectives: We aimed to determine the relationship between usual dietary intake and accurately measured liver fat content in a multiethnic population. Methods: Participants from the Multiethnic Cohort were recruited into the cross-sectional Adiposity Phenotype Study including women and men aged 60–77 y and 5 race/ethnic groups (African American, Japanese American, Latino, Native Hawaiian, and white). They filled out a detailed FFQ and underwent abdominal MRI for liver fat quantification and whole-body DXA for total adiposity. Intake of a priori –selected dietary factors (total and macronutrient energy, specific micronutrients, and food groups) was analyzed in relation to liver fat by estimating the mean percentage liver fat for quartiles of each dietary factor in a general linear model that adjusted for age, sex, race/ethnicity, percentage body fat, and daily energy intake (kcal/d). Results: In total, 1682 participants (mean age: 69.2 y; 51% female) were included. Mean ± SD liver fat percentage was 5.7 ± 4.6. A significant positive association with liver fat was found across quartiles of percentage energy from fat, saturated fat, cholesterol, total red meat, red meat excluding processed red meat, and coffee (Bonferroni-adjusted P -trend < 0.05). A significant inverse association was observed for dietary fiber, vitamin C, and vitamin E (Bonferroni-adjusted P -trend < 0.05). Conclusions: This study of ethnically diverse older adults shows that certain dietary factors, in particular red meat and saturated fat from red meat, were strongly associated with liver fat, whereas dietary fiber was inversely associated with liver fat, replicating some of the previous studies conducted mostly in whites.